ANALISIS PRASANGKA JUAL BELI JABATAN DALAM PELAKSANAAN TES PERANGKAT DESA DI KABUPATEN KEDIRI - , Titis Rahayuningtiar (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This research discusses the phenomenon of prejudice in the selection process of village officials by focusing on its impact on public administration ethics. The practice of buying and selling positions, as a threat to the principle of meritocracy, can undermine village governance and public trust in village institutions. The research method used an analytical descriptive qualitative approach to provide an in-depth description of the phenomenon of the prejudice of buying and selling positions in the implementation of the village apparatus test in Kediri District. The results showed that the alleged practice violated the ethical principles of public administration, including transparency, accountability, and public participation. The negative impacts include a decline in the quality of public services and the reputation of village institutions. In conclusion, there is a need to improve the recruitment system and increase understanding of public administration ethics at the village level. Preventive and curative measures should be implemented to prevent and tackle the practice of buying and selling positions. Strengthening internal and external supervision is also needed to maintain the integrity of village officials. This study contributes to the understanding of the practice of buying and selling positions at the local level and proposes solutions to improve the integrity and effectiveness of village public administration.